A CASE OF Aeromonas hydrophila INFECTION DUE TO CAPTIVITY-INDUCED STRESS IN A SPECTACLED CAIMAN ( C aiman crocodilus) - K. T. Kim; D. Kwak (Journal of Animal and Plant Sciences, 2013)
Aeromonas hydrophila is a facultative anaerobic, Gram-negative bacterium often regarded as an opportunistic pathogen in animals. A 4-year-old male spectacled caiman (Caiman crocodilus) died after 4 days of anorexia and depression. Necropsy was performed during which mild swelling and ash gray discoloration of the liver was observed. Additionally, the gall bladder was enlarged and elongated. Rod-shaped bacteria were found in the liver by Giemsa staining and identified as A. hydrophila. The animal had been exposed to stressful conditions prior to death, and decreased immune system functioning may have contributed to A. hydrophila infection of the animal.
Keywords: Aeromonad; exhibition stress; pathology; spectacled caiman